1997
DOI: 10.1016/s0146-6380(96)00131-3
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid chronology of the Lower Pleistocene deposits of Venta Micena (Orce, Granada, Andalusia, Spain)

Abstract: Abstract-This paper deals with a model adjustment for the estimation of age by means of amino acid racemization analysis. Two model families were obtained on the basis of the different genera of mol luscs analysed, and were applied to a palaeontological site located in the Cullar-Baza basin: "Venta Micena" (Orce, Granada). The analytical results obtained from the study of fossil gastropods have pro vided a very coherent average dating of 983 ± 58 Ky, this coinciding to a large extent with the most widespread p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
(11 reference statements)
0
33
0
1
Order By: Relevance
“…1.3 Ma (Ortiz et al, 2002;Clarke and MurrayWallace, 2006) but in the Canary Islands only the last 600 ka. For the present work, many samples have been submitted for dating with the AAR method (Torres et al, 1997;Ortiz et al, 2002Ortiz et al, , 2004 to the Biomolecular Stratigraphy Laboratory of the Polytechnical University of Madrid.…”
Section: Methodsmentioning
confidence: 99%
“…1.3 Ma (Ortiz et al, 2002;Clarke and MurrayWallace, 2006) but in the Canary Islands only the last 600 ka. For the present work, many samples have been submitted for dating with the AAR method (Torres et al, 1997;Ortiz et al, 2002Ortiz et al, , 2004 to the Biomolecular Stratigraphy Laboratory of the Polytechnical University of Madrid.…”
Section: Methodsmentioning
confidence: 99%
“…3). Addition ally, Torres et al (1994a) used aminochronology to date the travertine of the + 90 terrace of the Trabeque-EscabasGuadiela rivers to 733 ± 140 ka, at the beginning of the Bruhnes chron, and Silva et al (1999) found remains of M ammuthus meridionalis (Early Pleistocene) in a terrace equivalent to the + 80 85 terrace of the Manzanares River. The wider recognition of this boundary can be achieved by regional correlation of terraces.…”
Section: Early Pleistocenementioning
confidence: 99%
“…3). Torres et al (1994a) dated the +20 m terrace of the Trabeque-Escabas-Guadiela rIvers as 18.2 ±1.4 to 10.5 ±4.7ka (Th/U). Gladfelter (1971Gladfelter ( , 1972 and Preece (1991) provided 14C ages between 9940 ± 120 and 6210 ± 85 BP for the +4 m terrace of the upper Henares River.…”
Section: Late Pleistocene and Holocenementioning
confidence: 99%
“…Gastropod shells are particularly useful for amino acid racemisation/epimerisation dating, as their non-porous shell structure minimises contamination (Hare and Mitterer, 1968). Thus, it has been successfully used for the dating of gastropod shells (Goodfriend, 1987a(Goodfriend, , 1991(Goodfriend, , 1992Goodfriend and Mitterer, 1988;Meyer, 1992;Torres et al, 1997;Ortiz et al, 2002;Brooke et al, 2003).…”
Section: Introductionmentioning
confidence: 99%